2014
DOI: 10.5152/dcbybd.2013.04
|View full text |Cite
|
Sign up to set email alerts
|

Opinions for Family Presence During Cardiopulmonary Resuscitation in Turkey: A Literature Review

Abstract: Amaç: Bu derlemenin amacı, Türkiye'de kardiyopulmoner resüsitasyon sırasında ailenin bulunmasıyla ilgili çalışmaları değerlendirmektir.Gereç ve Yöntemler: Türkiye'de kardiyopulmoner resüsitasyon sırasında ailenin bulunması ile ilgili çalışmalar incelendi. Bu literatür incelemesi bilgisayar ortamında PubMed/ MEDLINE veritabanları kullanılarak yapıldı. Türkiye'de kardiyopulmoner resüsi-tasyon sırasında ailenin bulunması ile ilgili beş makale bulundu. Bu beş çalışma amaç, örneklem, yöntem, sonuç ve çıkarımları iç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 37 publications
0
7
1
Order By: Relevance
“…Finally, nationality and, to a minor extent, gender demonstrated a signi cant effect on healthcare providers' opinions to several survey items measuring HP perceptions of FPDR (see Table 4). The current study outcomes are contrary to the outcomes of Iran, Singapore, and Turkey, where the majority of ED physicians and nurses are against FPDR (6,7,13). But it is important to note that the study outcomes are in support of outcomes measured in Saudi Arabia, as well as a Needs Assessment for FPDR conducted by the American Heart Association, and a systematic review of four randomized controlled trials that looked at the psychological outcomes of FPDR on family relatives (10,20,21).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Finally, nationality and, to a minor extent, gender demonstrated a signi cant effect on healthcare providers' opinions to several survey items measuring HP perceptions of FPDR (see Table 4). The current study outcomes are contrary to the outcomes of Iran, Singapore, and Turkey, where the majority of ED physicians and nurses are against FPDR (6,7,13). But it is important to note that the study outcomes are in support of outcomes measured in Saudi Arabia, as well as a Needs Assessment for FPDR conducted by the American Heart Association, and a systematic review of four randomized controlled trials that looked at the psychological outcomes of FPDR on family relatives (10,20,21).…”
Section: Discussionmentioning
confidence: 60%
“…In Turkey, a literature review was performed for ve articles relating to family presence during cardiopulmonary resuscitation. The study concluded that Healthcare professionals were not in support of family presence, and those who had taken part in family presence during cardiopulmonary resuscitation had negative experiences (7). A study in Saudi Arabia looked at the attitudes of acute care nurses' toward FPDR in the largest hospitals in the ve geographic regions of Riyadh City.…”
Section: Discussionmentioning
confidence: 99%
“…In Turkey, a literature review was performed for five articles relating to family presence during cardiopulmonary resuscitation. The study concluded that Healthcare professionals were not in support of family presence, and those who had taken part in family presence during cardiopulmonary resuscitation had negative experiences [7].…”
Section: Discussionmentioning
confidence: 96%
“…In general, items [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] receiving a higher score on the Likert scale represented a higher agreement to FPDR by the study participants ("Strongly Agree" = 5, "Agree" = 4, "Neutral" = 3, "Disagree" = 2, Strongly Disagree = 1). Items 9,11,12,15,17,18,19, 20 and 22 were reverse-coded, where selecting "Strongly Agree" represented a more negative perception of FPDR and as such, the typical Likert score of 5 was recoded to be a score of 1 (see Table 3).…”
Section: Knowledge and Participation In Fpdrmentioning
confidence: 99%
See 1 more Smart Citation